GEOMA (GEOMETRI MATEMATIKA) APPLICATION AS GEOGEBRA-BASED LEARNING MEDIA TO TRAIN SPATIAL ABILITY - Siti Mutiah; Mutaqin Anwar; Setiani Yani (Universitas Muhammadiyah Metro, 2023)
The problem on this research is the low spatial sense ability in geometry material. Students have difficulty transforming literacy into geometric shapes. Thus, it required learning media to support the students in learning the geometry material. This research aims to develop GeoGebra-based mathematics learning media to practice spatial sense ability in geometrical materials for senior high school level practically, effectiveness, and feasibility. This research and development used the ADDIE development model. It covered analyzing needs, designing, developing, implementing the product, and evaluating at each stage. The final result of the development of this learning media is the GEOMA application that has a level of practicality, effectiveness, and feasibility with the category "good" to be used as a medium of learning high school geometry. Latar belakang penelitian ini adalah rendahnya kemampuan spatial sense  pada materi geometri. Siswa kesulitan mentransformasi dari bentuk literasi ke bentuk geometrinya, sehingga dibutuhkan sebuah media pembelajaran yang dapat memudahkan siswa mempelajari materi geometri. Penelitian ini bertujuan mengembangkan media pembelajaran matematika berbasis GeoGebra untuk melatih kemampuan spatial sense pada materi geometri SMA yang layak, praktis, dan efektifitas. Penelitian dan pengembangan ini menggunakan model pengembangan ADDIE. Tahapan penelitian yang dilakukan yaitu menganalisis kebutuhan produk, merancang, mengembangkan, uji coba penggunaan produk, dan evaluasi di setiap tahapannya. Hasil akhir dari pengembangan media pembelajaran ini adalah aplikasi GEOMA yang memiliki tingkat kepraktisan, efektif, dan kelayakan dengan kategori "baik" untuk digunakan sebagai media pembelajaran geometri SMA.